Spielen, Lernen, Arbeiten in Lernwerkstätten Facetten der Kooperation und Kollaboration - Stadler-Altmann, Ulrike; Schumacher, Susanne; Emili, Enrico Angelo; Dalla Torre, Elisabeth (Lernen und Studieren in Lernwerkstätten, 2020)
Along the action forms of playing, learning and working, the most diverse forms of cooperation and collaboration in and between learning workshops are discussed and research approaches as well as facets of pedagogical learning workshop work are described. It becomes clear that playing without learning and working, learning without playing and working and working without playing and learning is unthinkable. In this way, a monoculture of playing, learning and working is overcome and a reciprocal conditionality in pedagogical action becomes visible. Learning workshops are also places in which being at work or being active, discourse and reflection in learning, work and play situations are the focus and in which cooperation, which may be understood pragmatically, can become collaboration based on the subject matter.